Evaluation of the motor profile in children of Teresina - PI with Autistic Spectrum Disorder (ASD) - Teixeira, Bruna Marques (2019)
One of the major comorbidities associated with autism in children is directly related to motor performance deficit as a response to movement. Children with Autism Spectrum Disorder (ASD) have a number of motor changes, with delays in coordination, resulting in deficits in learning fine and complex motor skills. The objective of the study was to evaluate the motor profile of children with ASD. It is a clinical, observational, transversal, prospective, quantitative and descriptive study. The study was carried out with 20 children diagnosed with ASD, of both sexes, aged between 05 and 11 years, in an Association of autistic children in Teresina-PI. The Motor Development Scale (EDM) was used to carry out the study, which includes diverse tests and different difficulties that allow to evaluate the level of motor development. The results revealed a significant difference between motor age and chronological age, with a lower and lower motor development level.  It was possible to observe that children with ASD present general motor age inferior to chronological age.